Single anastomosis sleeve ileal bypass a single anastomosis sleeve jejunal bypass in the surgical treatment of severe obesity - Hrubý, M; Vodičková, D (Rozhledy v chirurgii, 2024)
Bariatric surgery has been proven to be an effective method in the treatement of morbid obesity. The ideal bariatric procedure should be effective, easy to perform and safe. Sleeve gastrectomy and RYGB currently represent the most frequently used bariatric/metabolic procedures. However, they have a certain percentage of complications and post-operative morbidity and also they fail in some patients. These facts lead to the development of new surgical procedures, which also include single anastomosis sleeve ileal bypass (SASI) and single anastomosis sleeve jejunal bypass (SASJ). These procedures combines the advantages of restrictive and malabsorptive operations at the same time reducing the risk of nutrient deficiencies by maintaining passage through all the alimentary tract. The results so far are encouraging, further research and especially longer-term results are necessary.
Keywords: jejunum; Gastrectomy; Jejunum; Retrospective Studies; lidé; SASI; výsledek terapie; sleeve jejunal bypass; Laparoscopy; gastrektomie; žaludeční bypass; Ileum; ileum; bariatrická chirurgie; Gastric Bypass; SASJ; Anastomosis, Surgical; retrospektivní studie; Humans; sleeve ileal bypass; anastomóza chirurgická; bariatric surgery; Bariatric Surgery; laparoskopie; Treatment Outcome; Obesity, Morbid; morbidní obezita